STRUCTURAL AND SEMANTIC FEATURES OF WORD PAIRS IN ENGLISH AND UZBEK (International journal of artificial intelligence, 2025)
This article explores the structural and semantic features of word pairs (binomials) in the English and Uzbek languages from a contrastive linguistic perspective. Word pairs are idiomatic or semi-fixed combinations of two words that are frequently used in both everyday and literary discourse. By analyzing their structure (morphological and syntactic patterns) and semantic relationships (synonymy, antonymy, collocation), the study aims to identify the commonalities and differences between the two languages. The findings contribute to better understanding of phraseological systems in typologically different languages and inform translation, language teaching, and lexicography.